Aplikasi Nanoteknologi pada Energi Terbarukan untuk Peningkatan Efisiensi Sistem Penyimpanan Energi - Agus Hariyanto; Rosiana Romadon (CV. Aksara Global Akademia, 2023)
This research explores the role of nanotechnology in enhancing energy storage systems for renewable energy applications. The study aims to evaluate the potential of nanomaterials, including carbon nanotubes, graphene, and fullerenes, in improving the performance of energy storage devices, specifically batteries, by focusing on their ability to enhance energy conversion efficiency, storage capacity, and battery lifespan. A case study was conducted using a prototype battery incorporating these nanomaterials, connected to a photovoltaic system to simulate real-world energy production conditions. The methodology included testing key parameters, such as energy conversion efficiency, charging time, and battery degradation through multiple charge-discharge cycles. The findings showed a significant improvement in energy conversion efficiency, with the nanomaterial-based batteries outperforming conventional batteries by up to 20%. Additionally, the nanomaterial-based batteries demonstrated an increased storage capacity and longer cycle life, maintaining performance after hundreds of charge-discharge cycles. Nanomaterials contributed to these improvements by enhancing electrical conductivity, reducing internal resistance, and preventing degradation that typically occurs in conventional batteries during prolonged use. Furthermore, nanostructured coatings on the electrodes were found to improve light trapping and anti-reflection capabilities, which directly contributed to the higher efficiency of the battery. This research highlights the transformative potential of nanotechnology in energy storage systems, offering a promising solution to the intermittency challenges of renewable energy sources such as solar and wind. The study also suggests that further research is needed to explore other nanomaterials, scale up the technology for industrial applications, and integrate smart energy management systems to optimize energy storage in renewable energy systems.